PEMBIASAAN KEDISIPLINAN SISWA DI MI AL-ADNANI KAYANGAN JOMBANG - Laiyil Liyah Cahya Fitri; Muslih, Imam (PGMI UNHASY, 2024)
This research discusses the habituation of student discipline at MI Al-Adnani Kayangan Jombang. The objectives of this research are: 1). observing the habituation of student discipline at MI Al-Adnani Kayangan Jombang. 2). Observing teacher obstacles in accustoming students to discipline at MI Al-Adnani Kayangan Jombang. 3). Observing teacher solutions to overcome obstacles to student discipline habits at MI Al-Adnani Kayangan Jombang. This research uses qualitative research with a descriptive approach. The data collection techniques used were observation, interviews and documentation. The results of this research are 1). The habit of discipline towards increasing student discipline cannot be separated from the example of the teachers where teachers become role models/uswatu hasanah, consistent in implementing the rules such as before lessons begin. Students are expected to participate in congregational Dhuha prayers at the mosque, students must be present at school. 2). The discipline habits of students at MI AL-Adnani Kayangan, Diwek, Jombang include lack of self-awareness, laziness (lazy nature) and dishonest character who still likes to lie. 3). The solution used by teachers in resolving obstacles to the discipline of students at MI AL-Adnani Kayangan, Diwek, Jombang is by means of intense communication with fellow teachers and parents, imposing educational punishments or sanctions and by providing supervision and control.